The Urgency of Reorganizing Independent State Institutions in Realizing a Democratic and Constitutional Government System - Rifandanu, Farel (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
Since the Amendment of the 1945 Constitution, the development of state institutions has exercised state power by rearranging existing institutions, forming new institutions, and even independent state institutions. The presence of these institutions can strengthen Indonesia's position as a democracy and a modern rule of law. However, in its development, these independent state institutions began to arise various problems that triggered public distrust of these institutions. Therefore, it is necessary to re-establish these independent institutions to realize a democratic and constitutional system of government.